Cost analysis based on performance indicators during Healthcare Reform Plan in selected educational hospitals - Pouran Raeissi; Farbod Ebadi Fard Azar; Aziz Rezapour; Mohammad Afrouzi; Saeed Sheikh Gholami; Noureddin Niknam (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Hospitals are the main axis of health-care reforms or national health plans; therefore, accurate recognition of hospital costs based on operational indexes to these plans is necessary. The impact of implementing national health plans on the performance of health systems is ambiguous and misleading; therefore, the aim of this study was to assess the impact of Healthcare Reform Plan (HRP) on the micro level (e.g., educational or university hospitals). METHODS: This study was a descriptive retrospective study that research variables are checked in 1 year before and mean of 3 years after implementation of HRP by self-administrated checklist in selected public-educational hospitals covered by the medical universities in Tehran. The final analysis of the data was performed using cost-performance ratio and independent t-test for comparing the variables' changes before and after HRP. RESULTS: Unlike adjusted hospitalization costs, most operational indexes were not significant. The per capita cost adjusted of hospitalization in first and mean of 3 years after HRP increased 49.49% and 16.31%, respectively (P < 0.001), the adjusted cost per day was increased by 24.48% and 21.46% (P < 0.001), and adjusted cost per bed was increased 47.06% and 20.07% compared to before HRP (P < 0.001). CONCLUSION: Given the lack of alignment in adjusted cost changes in exchange for functional indicators, certainly, it cannot be argued that HRP had a favorable or undesirable effect on the hospitals.